2009
DOI: 10.1111/j.1551-2916.2009.02978.x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Rearrangement and Pore Space Coarsening During Solid‐State Sintering

Abstract: Coarsening of porosity during sintering has been observed in powder compacts of metallic, ceramic, and amorphous materials. Monitoring and modelling of the growth of individual (closed) pores in the late sintering stages are well established. Porosity is interconnected up to very high densities. Coarsening of the continuous pore space takes place during the initial and intermediate sintering stages. This coarsening is caused by localized transport of atoms or molecules (diffusion or viscous flow) as well as by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 73 publications
(108 reference statements)
4
36
0
1
Order By: Relevance
“…The above porosity increase has been attributed to pore coarsening in case of SPS TBCs. Exner et al explained the pore coarsening effect in case of several powder compacts during solid state sintering by saying that the pore coarsening can be caused by localized transport of atoms/molecules due to diffusion and or bulk particle rearrangement [27]. Hence, apart from the anticipated microstructural change caused by sintering, the possibility of pore coarsening that might take place in certain conditions and be responsible for increase in the total porosity as noted in coatings Exp-2 and Exp-3, should also be borne in mind to explain the results observed.…”
Section: Microstructural Changes After Heat Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The above porosity increase has been attributed to pore coarsening in case of SPS TBCs. Exner et al explained the pore coarsening effect in case of several powder compacts during solid state sintering by saying that the pore coarsening can be caused by localized transport of atoms/molecules due to diffusion and or bulk particle rearrangement [27]. Hence, apart from the anticipated microstructural change caused by sintering, the possibility of pore coarsening that might take place in certain conditions and be responsible for increase in the total porosity as noted in coatings Exp-2 and Exp-3, should also be borne in mind to explain the results observed.…”
Section: Microstructural Changes After Heat Treatmentmentioning
confidence: 99%
“…At these temperatures, significant microstructural changes occur, which may affect the lifetime and functional performance of the TBCs [26,27]. Due to the presence of extremely fine as well as coarse pores in SPS sprayed YSZ layers [20], it is important to understand how these pores respond to sustain exposure to high temperatures and how the accompanying changes affect the thermal conductivity of the TBC.…”
Section: Introductionmentioning
confidence: 99%
“…Our current inadequate understanding of sintering kinetics can in part be traced to the experimental difficulty of tracking microstructural changes in three dimensions (8). With recent advances in 3D imaging, however, researchers can now perform time-resolved measurements of the true size, shape, and interconnectivity of particles and pores (9)(10)(11)(12), from which it may be possible to pin down the atomic-level mechanism(s) underlying each stage of sintering.…”
mentioning
confidence: 99%
“…With recent advances in 3D imaging, however, researchers can now perform time-resolved measurements of the true size, shape, and interconnectivity of particles and pores (9)(10)(11)(12), from which it may be possible to pin down the atomic-level mechanism(s) underlying each stage of sintering. Of particular interest in this regard is the 3D rearrangement of particles that occurs during early-stage sintering (8,13), which can significantly affect subsequent densification but is hardly accessible from 2D cross-sections. In a recent experiment, Grupp et al (12) observed individual particle rotations as large as 8°during the sintering of loosely packed…”
mentioning
confidence: 99%
“…After initial crystal misorientations at particle contacts have been introduced by the random orientation of each powder particle, the system will tend to reach a state with lower grain boundary energy by adjusting the misorientations [12][13][14][15] . Clear experimental evidence of particle motion during sintering was obtained in previous studies for one-dimensional rows of powder particles and for two-dimensional particle arrays as these situations can be easily observed with traditional methods [16][17][18] . A quantitative analysis of three-dimensional particle systems is just about to become feasible and is expected to yield a clearly different picture, because other than in 1D or 2D model systems, particle movements in 3D are highly frustrated due to the packing of the particles.…”
mentioning
confidence: 99%